Perspectives on institutional change - water management in Europe - Insa Theesfeld; Frauke Pirscher (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
CONTENTS: Mapping institutional change... 3, Insa Theesfeld, Frauke Pirscher; Affordability as an institutional obstacle to water-related price reforms... 9, Erik Gawel, Wolfgang Bretschneider; Analysing the shortcomings of the Ukrainian urban waste water sector - Institutional options for modernisation ... 35, Herwig Unnerstall, Nina Hagemann; Gemeinschaftsgüter und Gemeinwohl - Theoretischer Erkenntnisgehalt und praktische Relevanz für die Regionalentwicklung am Beispiel von Wasserinfrastrukturen und Kulturlandschaften ... 55, Andreas Röhring, Timothy Moss, Ludger Gailing, Rita Gudermann; Explaining top-down institutional design: The introduction of River Basin Management in Portugal... 85, Andreas Thiel, Catrin Egerton; Decentralization failures in post-socialist fishery management ... 107, Insa Theesfeld, Oscar Schmidt
urn:nbn:de:gbv:3:2-18680
Keywords: 330